Habitat Configuration Alters Herbivory across the Tropical Seascape - Swindells, Kate L.; Murdoch, Robyn J.; Bazen, William D.; Harman, Nicholas W.; Unsworth, Richard K. F. (Frontiers in Marine Science, 2017)
There exists increasing evidence that top-down ecological processes such as herbivory are key in controlling marine ecosystems and their community structure. Herbivory has the potential to be altered by numerous environmental and ecological factors that operate at a variety of temporal and spatial scales, one such spatial factor is the influence of the marine landscape. We know little about how ecological processes such as herbivory change throughout the marine landscape and how the effects of these processes cascade. This is because most landscape scale studies observe species richness and abundance patterns. In terrestrial systems the landscape is well documented to influence ecological processes, but empirical evidence of this is limited in marine systems. In tropical seagrass meadows direct herbivory by parrotfish can be readily observed due to the clear hemispherical bite marks they leave on the seagrass. As with herbivory in other systems, this leaf consumption is thought to assist with leaf turnover, positively influencing leaf growth. Changes in its rate and extent are therefore likely to influence the characteristics of the plant. The faunal communities of seagrass meadows alter with respect to changes in the landscape, particularly with respect to connectivity to adjacent habitats. It might therefore be expected that a key ecological process such as herbivory will change with respect to habitat configuration and have cascading impacts upon the status of the seagrass. In the present study we examined indirect evidence of parrotfish grazing throughout the marine landscape and assessed this relative to plant condition. Seagrasses in locations of close proximity to mangroves were found to have double the amount of parrotfish grazing than sites away from mangroves. Evidence of herbivory was also found to be strongly and significantly negatively correlated to the abundance of plant attached epicover. The decreased epicover in the presence of elevated herbivory suggests increased leaf turnover. These results indicate that seagrass may have higher levels of ecosystem resilience in the presence of mangroves. Our research highlights how ecological processes can change throughout the marine landscape with cascade impacts on the resilience of the system.